Linear Free Vibration Analysis of Tapered Rectangular Cantilevered Timoshenko Beams using Energy Field Meth-od - raffi, Shaik Mahmad; Rao, Ch. Tirumala (International Journal of Engineering and Technology, 2018)
Here in this paper we discuss about Energy field method. There are many methods to evaluate the natural frequency of the structures but in this research paper the authors developed a method called â€œEnergy field methodâ€ which reduces computational efforts compared with the other methods and which is successfully applied for the Cantilever boundary condition of a tapered (rectangular cross section) Timoshenko beam and calculated the fundamental frequency parameter values and compared the results with existing literature. To confirm the precision, coherence and adaptability of the model these resultant values are also compared with modal structural analysis values in Ansys10 software.